Hybrid Ionic Liquid–Silica Xerogels Applied in CO2 Capture - Aline S. Aquino (Applied Sciences, 2019)
The imidazolium-based ionic liquids (ILs) are solvents known for selectively solubilizing CO2 from a gas CH4/CO2 mixture, hence we have produced new hybrid adsorbents by immobilizing two ILs on xerogel silica to obtain a solid−gas system that benefits the ILs’ properties and can be industrially applied in CO2 capture. In this work, the ILs (MeO)3Sipmim.Cl and (MeO)3Sipmim.Tf2N were used at different loadings via the sol−gel process employing a based 1-methyl-3-(3-trimethoxysylilpropyl) imidazolium IL associated to the anion Cl− or Tf2N− as a reactant in the synthesis of silica xerogel. The CO2 adsorption measurements were conducted through pressure and temperature gravimetric analysis (PTGA) using a microbalance. SEM microscopies images have shown that there is an IL limit concentration that can be immobilized (ca. 20%) and that the xerogel particles have a spherical shape with an average size of 20 µm. The adsorbent with 20% IL (MeO)3Sipmim.Cl, SILCLX20, shows greater capacity to absorb CO2, reaching a value of 0.35 g CO2 / g adsorbent at 0.1 MPa (298 K). Surprisingly, the result for xerogel with IL (MeO)3Sipmim.Tf2N shows poor performance, with only 0.05 g CO2 / g absorbed, even having a hydrophobic character which would benefit their interaction with CO2. However, this hydrophobicity could interfere negatively in the xerogel synthesis process. The immobilization of ionic liquids in silica xerogel is an advantageous technique that reduces costs in the use of ILs as they can be used in smaller quantities and can be recycled after CO2 desorption.